2019
DOI: 10.3311/ppci.12816
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gilsonite Use on Storage Stability of Styrene-butadiene-styrene Modified Bitumen

Abstract: Styrene-butadiene-styrene (SBS) polymer is one of the most preferred additives to improve performance in hot mix asphalt pavements. The storage instability, in other words, the separation of a polymer-rich phase from the bitumen-rich phase in the course of storage and transportation is one of the prevalent problems in SBS modified bitumen. The present study attempted to obtain modified bitumen at the same performance level with the SBS modified bitumen, but stable with respect to the storage stability. For thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Yalçın et al [41] carried out experimental work to investigate the effect of using gilsonite on the storage stability of SBS-modified asphalt binder. The results of penetration tests indicated that the most stable modified binders based on storage stability were 18% gilsonite and 2% SBS + 13% gilsonite.…”
Section: Asphalt Modified With Gilsonite In Combination With Other Additivesmentioning
confidence: 99%
See 4 more Smart Citations
“…Yalçın et al [41] carried out experimental work to investigate the effect of using gilsonite on the storage stability of SBS-modified asphalt binder. The results of penetration tests indicated that the most stable modified binders based on storage stability were 18% gilsonite and 2% SBS + 13% gilsonite.…”
Section: Asphalt Modified With Gilsonite In Combination With Other Additivesmentioning
confidence: 99%
“…Other tests used in assessing the performance of the gilsonite-modified binder at high temperatures and at low temperatures were DSR and BBR, respectively. Based on the available literature, the gilsonite improved the performance of asphalt binder in high temperatures through increased shear strength of the modified binder [12,15,17,28,37,39,41]. However, the reviewed studies confirmed the weakness of gilsonite as a modifier for asphalt binder in terms of its properties at low temperature, due to the stiffness values of gilsonite-modified asphalts increasing with increasing gilsonite concentration [15,38,39].…”
Section: Critical Evaluation Of Gilsonite As Asphalt Modifiermentioning
confidence: 99%
See 3 more Smart Citations